2022
DOI: 10.1002/cam4.4542
|View full text |Cite
|
Sign up to set email alerts
|

Myelin and lymphocyte protein serves as a prognostic biomarker and is closely associated with the tumor microenvironment in the nephroblastoma

Abstract: Nephroblastoma, also known as Wilms' tumor (WT), is the most common renal tumor that occurs in children. Although the efficacy of treatment has been significantly improved by a series of comprehensive treatments, some patients still have poor prognosis. Myelin and lymphocyte (MAL) protein, a highly hydrophobic integrated membrane‐bound protein, has been implicated in many tumors and is also closely linked to kidney development. However, the relationship between MAL and WT has not yet been elucidated. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…A recent study revealed that increased expression of DEPDC1 leads to poor survival in patients with nephroblastoma ( 36 ). Su et al ( 5 ) found that DEPDC1 is highly expressed in nephroblastoma and associated with poor survival using database network analysis. The present study investigated the role and underlying mechanism of DEPDC1 in nephroblastoma progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study revealed that increased expression of DEPDC1 leads to poor survival in patients with nephroblastoma ( 36 ). Su et al ( 5 ) found that DEPDC1 is highly expressed in nephroblastoma and associated with poor survival using database network analysis. The present study investigated the role and underlying mechanism of DEPDC1 in nephroblastoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of treatment methods has led to long-term survival rate of >90% ( 4 ); thus nephroblastoma has one of the best prognoses among types of pediatric cancer. However, certain patients still experience poor prognosis due to cancer recurrence and metastasis ( 5 ). Therefore, discovering targeted biomarkers of nephroblastoma may contribute to understanding of the pathogenesis and metastatic mechanism and development of novel therapeutic strategies for management of patients with nephroblastoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports about promoter methylation of MAL-family genes in cancer are available only for MAL, MAL2, and MALL. Hypermethylation of MAL was found in BRCA [67,122], CESC [87], COAD-READ [77][78][79]81,82,123,124], ESCA [125], HNSC [70,71,74], Wilm's tumor [126], LUSC [83,84], STAD [75], and PRAD [127,128]. Hypermethylation of MAL2 was observed in malignant meningioma [110], and of MALL in COAD-READ [113], but not in CESC [85].…”
Section: Mal-family Gene Methylation In Cancermentioning
confidence: 93%
“…DEP domain containing 1 (DEPDC1) is an important modulator of the Wnt pathway, reported as a tumor-related gene that promotes carcinogenesis and is found to be upregulated in numerous cancer types [ 76 ]. DEPDC1 facilitates the malignant transformation of nephroblastoma by employing the Wnt/β-catenin signaling pathway, which may be modulated by forkhead box transcription factor 3a (FOXO3a) [ 77 ]. Su et al revealed that DEPDC1 was overexpressed in nephroblastoma and associated with poor prognosis.…”
Section: Wnt Signaling In Wilms Tumor (Nephroblastoma)mentioning
confidence: 99%